Sourcing and Global Distribution of Medical Supplies - Resnick, Adam C. (RAND Corporation, 2014)
The Department of Defense provides medical care to service members all over the world and must ensure that health care providers have the proper quantity and quality of medical materiel. RAND investigated opportunities to gain efficiencies in the logistics enterprise without sacrificing capability, notably through minimizing intermediate materiel handling, seeking greater value from commercial freight, and streamlining warehouse operations.